Thermodynamic analysis of olive oil mill wastewater steam reforming - Cláudio Rocha (2019)
A thermodynamic analysis of the steam reforming of olive oil mill wastewater (OMW) was performed in a traditional reactor (TR). The equilibrium compositions are calculated employing the Gibbs free energy minimization method (using Aspen Plus V8.8 (R) software). The simulations were performed at different temperatures (300-1000 degrees C), different pressures (1-20 bar) and different compositions of the OMW, which might differ considerably. It was found that the H-2 yield increases with the temperature up to a maximum value, while it continuously decreases with the pressure. In opposition, the water content in the feed increases the H-2 yield, thus providing opportunity to take advantage of the waste aqueous matrix. The optimum operating conditions for several OMW compositions, corresponding to either real or simulated effluents from different areas, were determined; this is a very important aspect that allows to assess, in advance, the potential of such waste valorization into green hydrogen production. Moreover, it was found a good agreement between the maximum H-2 yield obtained for each wastewater and the ones predicted based on their compositions. Coke formation was also accounted, which increases when decreasing either temperature or water content in the feed. However, for a water content in the feed greater than 60 wt.% (which is the case of most OMWs) there is no coke formation whatever the temperature and pressure (within the ranges used in this study) and for all the effluent compositions considered.